(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2019)
This article based on writer interest on New Order history, especially regarding the Ministry of State for Development and Environment Supervision. After research found that Emil Salim was the man behind the establishment of The Environment Ministry and acknowledged as the first minister in 1978 – 1993. However, the study focused on Emil Salim first period as Minister in 1978 – 1983. Thus, it will be interesting if Emil Salim role in the formation of the Ministry of State for Development and Environment Supervision and his policy as Minister from this sector has furthermore studied. This research intended to explain the formation process of the Ministry and analyzed Emil Salim policy on protecting the environment and managing development. This research used historical research methods that is heuristic, critic, and historiography. Based on the research, Emil Salim is an economist who trusted by the New Order government to manage development and environment. As a Minister, Emil Salim pioneered some policies for protecting and managing the environment. Some of his policies were Center for Environmental Studies in 1979, Kalpataru Award in 1981 and Product of Law in Constitution Number 4 the year 1982.